Hopalong Cassidy's Rustler Round-Up; Or, Bar-20 - Mulford, Clarence Edward, 1883-1956 (Salt Lake City, UT : Project Gutenberg, 2001)
"Hopalong Cassidy's Rustler Round-Up; Or, Bar-20" by Clarence Edward Mulford is a novel written in the early 20th century, capturing the adventurous spirit of the American West. The story centers around the main character, Hopalong Cassidy, and his friends at the Bar-20 ranch as they navigate conflict, camaraderie, and gunfights amidst the tumultuous setting of Buckskin, a small and rough town filled with cowboys and tension stemming from ranch rivalries. The opening of the book introduces Buckskin, a small Texas town characterized by its harsh conditions and a population rife with quirky characters. We learn about the ongoing feud between Buckskin and the nearby town of Perry's Bend, instigated by a violent past involving cowboys and gunmen, including Buck Peters, who had caused quite a stir. As tensions escalate into a series of skirmishes, the narrative unfolds with the introduction of the rustic camaraderie among Cassidy's friends, their banter, and their readiness to confront the brewing conflicts with humor and grit. The stage is set for a tale of adventure, challenges, and the brotherhood of cowhands fighting for their honor and livelihoods. (This is an automatically generated summary.)
Release date is 2001-03-01
Produced by Andrew Heath, and David Widger
Keywords: Western stories; Cassidy, Hopalong (Fictitious character) -- Fiction